2011
DOI: 10.1007/s00395-011-0211-y
|View full text |Cite
|
Sign up to set email alerts
|

Carbon monoxide exposure enhances arrhythmia after cardiac stress: involvement of oxidative stress

Abstract: Arrhythmias following cardiac stress are a key predictor of death in healthy population. Carbon monoxide (CO) is a ubiquitous pollutant promoting oxidative stress and associated with hospitalization for cardiovascular disease and cardiac mortality. We investigated the effect of chronic CO exposure on the occurrence of arrhythmic events after a cardiac stress test and the possible involvement of related oxidative stress. Wistar rats exposed chronically (4 weeks) to sustained urban CO pollution presented more ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 51 publications
2
36
0
Order By: Relevance
“…The mitochondrial ROS in AT was performed as previously described (2). Frozen fat tissue cross sections from CD-and HFHSD-fed mice were evaluated by measuring the level of mitochondrial superoxide (O 2 -) production quantified by MitoSox Red kit (Molecular probe, Invitrogen).…”
Section: Measurement Of Mitochondrial Rosmentioning
confidence: 99%
“…The mitochondrial ROS in AT was performed as previously described (2). Frozen fat tissue cross sections from CD-and HFHSD-fed mice were evaluated by measuring the level of mitochondrial superoxide (O 2 -) production quantified by MitoSox Red kit (Molecular probe, Invitrogen).…”
Section: Measurement Of Mitochondrial Rosmentioning
confidence: 99%
“…It is well documented that the binding of CO to cytochrome-c oxidase in the electron transport chain, as well as the interaction of CO with NO synthase (Heusch et al, 2010), generates reactive oxygen and nitrogen species (ROS and RNS) (Ide et al, 1999;Kaiser, 2005). Recently, we have shown that chronic CO exposure decreases the activity of the antioxidant enzymes superoxide dismutase, catalase, and glutathione peroxidase, increases that of thioredoxin reductase, and increases levels of malondialdehyde, the end-product of lipid peroxidation by ROS, thus confirming the presence of CO-induced oxidative stress (Andre et al, , 2011. These are all features that are typical of ventricular myocytes isolated from failing hearts.…”
Section: Experimental Evidence From Healthy Animal Modelsmentioning
confidence: 80%
“…Following exposure mimicking urban CO pollution, the Hb CO level of the animals was 4-6% on leaving the container but it was normalized to 2% after several hours. Despite these low CO concentrations, the animals developed pathological cardiac remodelling characterized by an increase of both posterior wall thickness and left ventricular fibrous tissue, without dilatation or hemodynamic changes (Andre et al, , 2011.…”
Section: Experimental Evidence From Healthy Animal Modelsmentioning
confidence: 99%
See 2 more Smart Citations